Pengaruh Pengalaman, Independensi, Gender Auditor Terhadap Kualitas Audit - Irma Suryani; Asep Efendi; Fitriana Fitriana (Ridwan Institute, 2021)
This research was conducted because of the number of cases of audit failure that mghasilka poor audit quality, alleged experience, independesi, gender auditor brpgaruh to the quality of audit supported by the inconsistencies of the results of previous research. The population in the study was a permanent auditor working atkap Central Jakarta registered in the IAPI 2019 directorate. The study population was 265 auditors. Determination of sample size using the Slovin formula. The sampling technique used was probability sampling and the number of samples in this study was 72 fixed auditors. The research method used is descriptive and verifikative method. Data analysis method uses multiple linear regression analysis using SPSS 20. The results prove that: (1) auditor experience in KAP Central Jakarta belongs to the high category (2) auditor independence in KAP Central Jakarta including the very high category (3) gender auditors in KAP Central Jakarta dominated by men, the results showed female auditors are better at auditing.( 4) The quality of auditors at KAP Central Jakarta is of a high category,(5)the auditor's experience has a negative and insignificant effect on the partial audit quality,(6) Independence has a positive and significant effect on the quality of the audit partially,(7) gender negatively and significantly affects the quality of the audit partially, (8)experience, independence, the auditor's gender affects the quality of the audit simultaneously.